2020
DOI: 10.2196/17884
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of (Non)Participation of Older People in Digital Health Research: Exergame Intervention Study

Abstract: Background The use of digital technologies is increasing in health care. However, studies evaluating digital health technologies can be characterized by selective nonparticipation of older people, although older people represent one of the main user groups of health care. Objective We examined whether and how participation in an exergame intervention study was associated with age, gender, and heart failure (HF) symptom severity. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 47 publications
2
31
1
Order By: Relevance
“…personality traits of the caregivers like level of self-esteem, neuroticism, confidence in the caregiver role and coping strategies [ 8 ]. Last but not least, despite the accurate sampling process and the careful recruitment process, the risk of the typical sampling bias should still be mentioned, as for instance, healthier and more educated older caregivers are more likely to participate in research studies (especially those involving technologies, such as TECH@HOME and UP-TECH [ 68 ]. Nonetheless we have minimized the likelihood of such risk, adjusting our analysis using available socio-economic variables.…”
Section: Discussionmentioning
confidence: 99%
“…personality traits of the caregivers like level of self-esteem, neuroticism, confidence in the caregiver role and coping strategies [ 8 ]. Last but not least, despite the accurate sampling process and the careful recruitment process, the risk of the typical sampling bias should still be mentioned, as for instance, healthier and more educated older caregivers are more likely to participate in research studies (especially those involving technologies, such as TECH@HOME and UP-TECH [ 68 ]. Nonetheless we have minimized the likelihood of such risk, adjusting our analysis using available socio-economic variables.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, selection bias may be present as individuals uncomfortable using these digital technologies may have self-selected out. Moreover, a previous study showed that people who agree to participate in digital studies, compared to those who do not, are younger; mostly male; and have better health, quality of life, socioeconomic status, and digital skills [ 15 ]. Therefore, our study included women of all ages.…”
Section: Discussionmentioning
confidence: 99%
“…Older people should be involved in the studies which conduct design and evaluations of digital health technologies that are relevant to them (Östlund 2015). It is especially relevant that participation of older people in evaluations of digital technologies is not selective, and that study participants reflect the full heterogeneity of the target populations (Merkel and Kucharski 2018;Poli et al 2019;Allemann and Poli 2020;Poli et al 2020). Policies, in turn, should go beyond the mere promotion of digital health by actively shaping and impacting on key barriers and factors preventing full opportunities for older users (Melchiorre et al 2018b).…”
Section: Conclusion: Towards a Conceptual Framework On Old-age Digitamentioning
confidence: 99%
“…Digital health technologies can have exclusionary and inequality effects on older people (Poli et al 2019;Poli et al 2020). Such effects must represent a major concern for research, policy and practice, as digital health technologies are increasingly utilized in health systems and evolve rapidly.…”
Section: Conclusion: Towards a Conceptual Framework On Old-age Digitamentioning
confidence: 99%